AB0840 Cross-Sectional and Longitudinal Association Between Types of Meniscal Pathology and Knee Pain: Data from the Osteoarthritis Initiative. (9th June 2015) - Eathakkattu Antony, B.S.; Driban, J.; Lyn Price, L.; Lo, G.; Ward, R.; Eaton, C.; Ding, C.; McAlindon, T.
Abstract : Background: Meniscal pathology is only weakly related to knee pain. The associations between different types of meniscal pathology and knee pain are unknown. Objectives: To explore the association of different types of knee meniscal pathology with knee pain and change in knee pain over 2 years. Methods: We selected a convenience sample of the Osteoarthritis Initiative (OAI) who had complete data for the OAI Bone Ancillary Project. A musculoskeletal radiologist reviewed the 24-month OAI magnetic resonance (MR) images for meniscal pathology by location within the medial and lateral menisci using a modified International Society of Arthroscopy, Knee Surgery, and Orthopaedic Sports Medicine (ISAKOS) meniscal tear classification system. For analyses, we reclassified the 10 original ISAKOS categories into 5 categories: normal, degenerative signal, morphological deformity, any tear (i.e., horizontal, horizontal flap, longitudinal-vertical, radial, vertical-flap, complex tear), and maceration. Total number of regions affected by meniscal pathology for each knee (0-6) was calculated by counting the number of regions that had any pathology. Knee pain was assessed using Western Ontario and McMaster Osteoarthritis Index (WOMAC) scale at 24 and 48 months. Knee pain at 24 months was categorized into 3 categories: 1) no or little pain (WOMAC pain score 0 or 1), 2) mild pain (WOMAC pain score 2 or 3), 3) moderate-severe pain (WOMAC pain score >3). Longitudinally, we categorized the change in pain into 3 categories based on the presence or absence of pain and a clinically meaningful change in pain (absolute change of 2 or relative change of 40%): 1) no pain or a meaningful decrease in pain (reference category), 2) pain but no change over time, and 3) meaningful increase in pain. Results: 465 participants were included in the analysis with mean age of 63.2 (9.1) years, 53% male, mean body mass index 29.5 (4.5) kg/m 2, 71% Kellgren-Lawrence grade ≥2, and 86% with any meniscal pathology. There was no association between presence of any meniscal pathology with knee pain or change in knee pain. Having all six meniscal regions affected with any pathology was associated with greater pain (OR:2.65) compared to those with normal menisci. However, having more affected meniscal regions was not related to an increase in pain. This pattern persisted when the number of regions affected by maceration was analyzed cross-sectionally and longitudinally. When we assessed the types of meniscal pathology, cross-sectionally, the only significant association was between meniscal maceration and greater knee pain (OR:2.89). Longitudinally, there was a significant association between morphological deformity (OR:1.46) and increase in knee pain over 2 years. Removing surgery or injury cases did not change our results. Conclusions: These results suggest that meniscal maceration is associated with higher knee pain that may not change over time. We hypothesize that morphological deformity may lead to maceration over time, which may explain why morphologic deformity is associated with increased pain over time. Further prospective studies are warranted to determine if discrete tear incidence is related to acute knee pain and if a subset of knees can then function without pain. Disclosure of Interest: None declared